Analisis Peran Sektor Pertanian Terhadap Pertumbuhan Ekonomi Di Kabupaten Gunungkidul Daerah Istimewa Yogyakarta - Erlinda Nur Khasanah; Nusron Habibur Rohman (Jurnal Khazanah Intelektual, 2024)
The flourishing land makes Indonesia to be an agricultural country. Majority of the population in Indonesia works in the agricultural sector. This sector is one of the sectors that supports the country's economy. One of the areas in the Special Region of Yogyakarta (DIY) Province that has quite large agricultural potential is Gunungkidul Regency. This research aimed to analyze the agriculture sector role in economic growth in Gunungkidul Regency. This research method used data analysis techniques consisting of the Klassen Typology Method and Location Quotient analysis. Based on the results of the Klassen Typology Method analysis, the agricultural sector in Gunungkidul Regency is in quadrant 2, namely the advanced but emphasized sector. Meanwhile, the results of the Typology Method analysis show the agricultural sector as one of the sectors in Gunungkidul Regency with a base or source of growth. This means that it was able to meet agricultural needs for its own region and the excess can be sold to other regions.